International Exchange Game: A Hidden Social Dilemma - Mcdonald, Don M. (Journal of management education, 2001)
This article presents a simple social dilemma designed to help 10 to 50 participants experience the value of winning with each other, not winning against each other, by maximizing both personal and group gain through cooperation. Participants are issued instruction sheets on which they collect each other’s signatures. Like a global economy in which everyone gives and takes, trust and interdependence are required for maximum personal gain. It has proven useful for experiencing value added, organization synergy, communication, trust, conflict resolution, and emergent leadership.